2010
DOI: 10.1002/bit.22771
|View full text |Cite
|
Sign up to set email alerts
|

Control of misincorporation of serine for asparagine during antibody production using CHO cells

Abstract: A recombinant monoclonal antibody produced by Chinese hamster ovary (CHO) cell fed-batch culture was found to have amino acid sequence misincorporation upon analysis by intact mass and peptide mapping mass spectrometry. A detailed analysis revealed multiple sites for asparagine were being randomly substituted by serine, pointing to mistranslation as the likely source. Results from time-course analysis of cell culture suggest that misincorporation was occurring midway through the fed-batch process and was corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 42 publications
(26 reference statements)
1
56
0
Order By: Relevance
“…155 Misincorporation of amino acids due to amino acid starvation can be eliminated by providing sufficient amounts of the specific amino acids. 149,150,154 It should be mentioned that low levels of misincorporation can occur naturally, 156 and it should not be a surprise that endogenous IgG molecules also contain low levels of sequence variants. Low levels of sequence variation may never be completely eliminated.…”
Section: Low Level Of Sequence Variantmentioning
confidence: 99%
“…155 Misincorporation of amino acids due to amino acid starvation can be eliminated by providing sufficient amounts of the specific amino acids. 149,150,154 It should be mentioned that low levels of misincorporation can occur naturally, 156 and it should not be a surprise that endogenous IgG molecules also contain low levels of sequence variants. Low levels of sequence variation may never be completely eliminated.…”
Section: Low Level Of Sequence Variantmentioning
confidence: 99%
“…Amino acid substitutions consistent with N>S have been reported before [8]. Seven N>S SVs with R 2 values above 0.9 were detected in the A/B mixing study and six in the B/C study; all were confirmed by manual inspection of the MS/ MS spectra (data not shown) and were unique to mAb B.…”
Section: Resultsmentioning
confidence: 49%
“…These SVs can take the form of Nterminal or C-terminal extensions due to DNA rearrangements [1,2], un-cleaved signal sequence [3], DNA point mutations [4,5], or amino acid substitutions [6][7][8]. In the case of amino acid misincorporations, SVs due to these events are likely to be ubiquitous in recombinant protein drugs [9], though challenging to detect.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, when cells are starved for Asn, the frequency of serine (Ser) incorporation at Asn positions increases during translation 189 . In spite of the fact that the underlying mechanisms have yet to be fully understood 190 , it is widely believed that the error rate during protein translation depends on factors such as the type of organism, the genotype and phenotype of the transfected cell lines, the codon usage, and the cell culture conditions 191 . When Asn abundance in the media is decreasing, Ser and Asn competition intensifies, leading to misacylation of tRNA Asn by Ser.…”
Section: Amino Acid Misincorporationmentioning
confidence: 99%
“…When Asn abundance in the media is decreasing, Ser and Asn competition intensifies, leading to misacylation of tRNA Asn by Ser. Serine substitution can be prevented by supplementing the culture medium with Asn 189,190 and regularly feeding Asn (6 g/L) throughout the culture to circumvent depletion of the latter 190 . Nonetheless, even at low levels of Asn in the medium, Ser misincorporation can be prevented through controlled feeding 190 , which may be a useful strategy to avoid important ammonia production as Asn synthetase is able to convert Asn to Gln, and eventually liberate ammonia to replenish the tricarboxylic acid cycle.…”
Section: Amino Acid Misincorporationmentioning
confidence: 99%